Control of Asystasia intrusa (Forssk.) Nees and Eleusine indica (L.) Gaertn. using selected doses of indaziflam on peat and mineral soil - Ahmad Rizki Lubis; Edison Purba; Teuku Irmansyah (Jurnal Agroekoteknologi, 2018)
Pre-emergent weed control is important in weed control strategy. Differences in characteristics of both peat and mineral soil may lead to a different result of weed control, especially pre-emergent herbicide application. Indaziflam, a pre-emergant herbicide, can be used as an alternative herbicide in overcoming weed resistance and tolerant weed.The objective of this study was to determine the efficacy of indaziflam at various doses on  peat and mineral soil using Asystasia intrusa (Forssk.) Nees and Eleusine  indica (L.) Gaertn. as indicator weeds. The experiment was arranged in randomized block design a factorial with four replicates. The first factor was dose of indaziflam (0; 12,5; 25; 37,5; 50; 62,5 and 75 g.ai/ha) and the second factor was type of soil (peat and mineral soil). The results showed that treatments of doses herbicide significantly affected the efficacy of indazfilam on A. intrusa and E. indica on peat and mineral soil. The efficacy was higher on mineral soil compared to peat soil.